Clinical Usefulness of 18F‐Fluorodeoxyglucose Positron Emission Tomography in the Diagnostic Algorithm of Advanced Entero‐Pancreatic Neuroendocrine Neoplasms. (8th November 2017) - Rinzivillo, Maria; Partelli, Stefano; Prosperi, Daniela; Capurso, Gabriele; Pizzichini, Patrizia; Iannicelli, Elsa; Merola, Elettra; Muffatti, Francesca; Scopinaro, Francesco; Schillaci, Orazio; Salgarello, Matteo; Falconi, Massimo; et al.
Abstract : Background: The role of 18 F‐fluorodeoxyglucose positron emission tomography ( 18 F‐FDG PET) in the diagnostic algorithm of entero‐pancreatic neuroendocrine neoplasms (EP NENs) is unclear because most available data derive from heterogeneous populations in terms of tumor biology and disease status at time of examination. The aim of this study was to determine the ability of 18 F‐FDG PET to identify patients with more aggressive disease among those with advanced EP NENs. Subjects, Materials, and Methods . Patients with advanced EP NENs and known disease status (progressive disease [PD] or stable disease [SD]) according to imaging procedures, who received 18 F‐FDG PET and computed tomography scans during a time frame of 1 month, were included. Results : A total of 93 patients, including 69 patients with pancreatic NENs and 24 patients with small‐intestine NENs, were included. At the time of study entry, 64 patients (68.8%) had PD, and the remaining 29 patients (31.2%) had SD. A total of 62 patients (66.7%) had positive 18 F‐FDG PET, whereas 18 F‐FDG PET was negative in the remaining 31 patients (33.3%). Overall, 18 F‐FDG PET sensitivity and specificity to detect PD were 90.6% and 86.2%, respectively, resulting in a diagnostic accuracy of 89.2%. A positive 18 F‐FDG PET was significantly associated with PD at the time of study entry ( p < .0001 at multivariate analysis). Although a higher proportion of 18 F‐FDG PET‐positive examinations were observed in patients with higher tumor grade ( p = .01), 53.8% of patients with grade 1 neuroendocrine tumors (NETs) had positive 18 F‐FDG PET, and 37.5% of patients with grade 2 NETs had negative 18 F‐FDG PET. Overall survival was significantly shorter in 18 F‐FDG PET‐positive patients (median: 60 months) in comparison with 18 F‐FDG PET‐negative patients (median not reached; p = .008). Conclusion : 18 F‐FDG PET has a high diagnostic accuracy to identify progression of disease with unfavorable clinical outcome in patients with advanced EP NENs. Knowledge of disease status and G grading are key factors for physicians to better select patients for whom 18 F‐FDG PET is clinically useful. Implications for Practice: The findings of the present study may help physicians dealing with advanced neuroendocrine neoplasms to select patients for whom 18 F‐fluorodeoxyglucose positron emission tomography is useful to predict poor clinical outcome. Abstract : The role of 18F‐FDG PET in the diagnostic algorithm of patients with advanced entero‐pancreatic neuroendocrine neoplasms is still to be established. This article reports on the ability of 18F‐FDG PET to identify cases of advanced entero‐pancreatic neuroendocrine neoplasms with more aggressive and unfavorable clinical outcomes.